2016
DOI: 10.1063/1.4967939
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of liquid-state anomalies in Stillinger-Weber models of water, silicon, and germanium

Abstract: We use molecular dynamics simulations to compare and contrast the liquid-state anomalies in the Stillinger-Weber models of monatomic water (mW), silicon (Si), and germanium (Ge) over a fairly wide range of temperatures and densities. The relationships between structure, entropy, and mobility, as well as the extent of the regions of anomalous behavior, are discussed as a function of the degree of tetrahedrality. We map out the cascade of density, structural, pair entropy, excess entropy, viscosity, and diffusiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 114 publications
5
37
0
1
Order By: Relevance
“…At lower densities, where no experiment are available at present, our simulations yield a maximum in η versus ρ and a minimum in D versus ρ. The minimum in D has been previously observed in simulations 17,22,[24][25][26]36 . To our knowledge, the maximum in η is found here for the first time.…”
Section: A Simulation Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…At lower densities, where no experiment are available at present, our simulations yield a maximum in η versus ρ and a minimum in D versus ρ. The minimum in D has been previously observed in simulations 17,22,[24][25][26]36 . To our knowledge, the maximum in η is found here for the first time.…”
Section: A Simulation Resultssupporting
confidence: 70%
“…35 We are aware of only two simulation studies of viscosity in the supercooled region under pressure. The first by Dhabal et al 36 reported D and η for the coarse-grained mW model (monatomic water), and the density dependence gave a minimum and a maximum for D and a minimum for η. However, because it omits the reorientation of hydrogen atoms, mW gives D three times higher and η three times lower than experimental values for water at ambient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…50 Using a classical Stillinger-Weber (SW) potential, the cases of water, silicon, and germanium have been investigated: 40,51 as in TIP4P/2005 water, the TMD line does not touch the LVS, and the latter does not show a retracing behavior. In addition, for SW silicon, a line of compressibility maxima has also been reported.…”
Section: Resultsmentioning
confidence: 99%
“…For the systems that we consider, the loci of density, isothermal compressibility and isobaric heat capacity extrema, and the liquid-vapor spinodal exhibit a strikingly similar pattern. 23,50,51,57,62 The location of the critical points and the thermodynamic property extrema are clearly system-dependent, but the various extrema loci exhibit many common features imposed by thermodynamics. 23,62 In particular, the loci of response function maxima merge asymptotically at the LLCP.…”
Section: Searching For Universality In the Pattern Of The Propertmentioning
confidence: 99%
“…Computer simulations, on the other hand, have shown that some molecular models of water exhibit liquid-liquid separation at deeply supercooled conditions. 22,[38][39][40][41][42][43][44][45][46][47][48] In tetrahedral systems, regardless of the existence or non-existence of the liquid-liquid separation (e.g., mW, [49][50][51] mTIP4P, 50 ST2, 52 The Journal of Chemical Physics ARTICLE scitation.org/journal/jcp TIP4P/2005, 53 TIP5P, 54 silicon, 30,31,55 silica, 32,33 and germanium 56 ), there is an underlying characteristic pattern of extrema lines for thermodynamic properties. The most wellknown is the line of density extrema, whose existence suggests a competition between low-density and high-density structures in the same liquid.…”
Section: Introductionmentioning
confidence: 99%